Systematic Design of a Butadiene Telomerization Process: The Catalyst Makes the Difference1. Issue 11 (26th September 2017) - Recker, Sebastian; Gordon, Charles M.; Peace, Amy; Redepenning, Christian; Marquardt, Wolfgang
Abstract: A conceptual design study for a butadiene telomerization process is presented. The impact of catalyst selection on the process economics is included into the design study by an optimization‐based approach relying on shortcut models. In comparison to the established process, investment cost of the novel designed process increase only marginally, while operating costs decrease by more than 75 %. Preliminary pilot‐plant experiments indicate, however, that the economically favorable reaction concept is not stable. Consequently, alternative immobilization strategies are briefly investigated to guide future research. Abstract : In this work, a comparative conceptual design study for a catalytic process for the telomerization of 1, 3‐butadiene with methanol is presented. The impact of the catalyst selection on the process economics is included by an optimization‐based approach.